Pengaruh Tingkat Kemiskinan dan Laju Pertumbuhan Ekonomi Terhadap IPM Kabupaten Tulungagung - Diella Vania Amelinda; Lucky Rachmawati (Universitas Negeri Surabaya, 2022)
The purpose of this study is to determine the impact of poverty and economic growth on the Human Development Index in Tulungagung Regency. In this study's discussion, quantitative approaches with an explanatory approach were used to determine the link between variables that affect the hypothesis. The data used is secondary data from BPS Tulungagung Regency, and it covers a 10-year period from 2011 to 2020. The HDI is affected negatively and significantly by the partial regression of the poverty rate and the rate of economic growth. The HDI is influenced by both the poverty rate and the rate of economic growth, and the coefficient of determination in this study is 98.5%.